DAYA SAING, KINERJA PERDAGANGAN, DAN DAMPAK LIBERALISASI PRODUK KEHUTANAN - Adrian Lubis (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2013)
Produk kehutanan Indonesia telah diliberalisasi sejak tahun 2007, namun kinerja perdagangannya belum membaik. Hal ini terlihat dari 127 pos tarif produk yang dibina Kementerian Kehutanan, hanya 34 pos tarif yang mengalami surplus perdagangan, 62 pos tarif mengalami defisit. Sebanyak 13 pos tarif dari 62 pos tarif yang defisit merupakan bahan baku yang banyak digunakan oleh industri kehutanan nasional. Berdasarkan hasil perhitungan Indeks Intra-Industry Trade dan Indeks Spesialisasi Perdagangan, serta hasil simulasi yang menggunakan GTAP GMig2, produk kehutanan yang memiliki daya saing tinggi adalah Pulp of Wood, jauh diatas daya saing produk Paper and Paper Board serta Woods and Article of Wood. Keterbatasan bahan baku menjadi penyebab utama gagalnya Indonesia untuk memanfaatkan liberalisasi perdagangan. Sebanyak 34 pos tarif yang surplus semenjak liberalisasi sebaiknya tetap diliberalisasi dan dijadikan produk ekspor utama. Adapun 13 pos tarif yang menjadi bahan baku utama industri nasional, meskipun mengalami defisit, sebaiknya tetap diliberalisasi. Sebanyak 49 pos tarif yang defisit dan tidak menjadi bahan baku utama sebaiknya diberlakukan trade remedies dan dijadikan produk sensitif. Since 2007 the forestry product has been liberalized, but its trading performance has not improved yet. From 127 product tariff lines fostered by the Ministry of Forestry, there are only 34 lines which gained trade surplus and 62 lines which experienced trade deficit. Out of 62 products tariff lines which experienced trade deficit, 13 products are raw materials which are widely used by forest industry. Based on the Intra-Industry Trade and Trade Specialization Indexes, as well as simulation results using the GTAP GMig 2, forestry product with high competitiveness is Pulp of Wood, far above the competitiveness of Paper and Paper Board and Woods and Articles of Wood. The limited availability of raw materials is the main cause of Indonesia’s failure to take advantage of trade liberalization. The 34 product tariff lines which experienced surpluses should remain liberalized and become the main export products. Although experiencing deficits, the 13 product tariff lines which are the main raw materials for the industrial sector should be continually liberalized, while the remaining 49 product tariff lines which are not key raw materials should be provided with trade remedies and they should be considered as sensitive products.